Coaching Psychology as a field of academic and applied psychology: methodological problems and research prospects - Antonova N. V. (Coaching psychology: methodology, theory, practice, 2025)
the article analyzes the development and methodological foundations of "Coaching Psychology" - a branch of academic and applied psychology that studies the psychological mechanisms of coaching as a support practice. The need for evidence-based coaching research is substantiated, the levels of evidence and the state of coaching research in Russia are considered. A classification of theoretical approaches to coaching within the framework of Coaching Psychology is provided. The prospects for research within the framework of Coaching Psychology and problems specific to Russia that hinder the development of scientifically based coaching in Russia are analyzed. A conclusion is made about the need to consolidate coaches to conduct evidence-based coaching research.
Keywords: теоретические подходы; психология коучинга; уровни доказательности; levels of evidence; практика сопровождения; evidence-based подход; перспективы исследований; coaching psychology; support practice; evidence-based approach; theoretical approaches; research prospects